English Phonology for Second Languange Learner - Safitri, Dea; Nurul Fhadilah; Yani Lubis (Tinta Emas Publisher, 2023)
This article provides an overview of English phonology for second-language learners. It employs qualitative methods with library research data collection techniques, specifically analyzing scientific journals and other relevant articles. The aim is to explore the intricacies of English phonology and its challenges for non-native speakers. The study delves into the various aspects of English phonetics and phonology, including segmental and suprasegmental features, vowel and consonant sounds, stress, intonation, and rhythm. It examines common pronunciation difficulties second language learners face and offers insights into practical strategies for improving pronunciation skills. The findings of this research contribute to the existing body of knowledge on English phonology and provide valuable guidance for educators and learners seeking to enhance their spoken English proficiency.